Participants' views and experiences from setting up a shared patient portal for primary and specialist health services- a qualitative study - Torunn Hatlen Nøst; Arild Faxvaag; Aslak Steinsbekk (BMC, 2021)
Abstract Background Recently, there has been an increasing focus among healthcare organisations on implementing patient portals. Previous studies have mainly focussed on the experiences of patient portal use. Few have investigated the processes of deciding what content and features to make available, in particular for shared portals across healthcare domains. The aim of the study was to investigate views on content and experiences from the configuration process among participants involved in setting up a shared patient portal for primary and specialist health services. Methods A qualitative study including 15 semi-structured interviews with persons participating in patient portal configuration was conducted from October 2019 to June 2020. Results Whether a shared patient portal for all the health services in the region should be established was not questioned by any of the informants. It was experienced as a good thing to have numerous participants present in the discussions on configuration, but it also was said to increase the complexity of the work. The informants considered a patient portal to be of great value for patient care, among other things because it would lead to improvements in patient follow-up and increased patient empowerment. Nevertheless, some informants advocated caution as they thought the patient portal possibly could lead to an increase in healthcare providers' workloads and to anxiety and worries, as well as to inequality in access to health care among patients. The findings were categorized into the themes 'A tool for increased patient involvement', 'Which information should be available for the patient', 'Concerns about increased workload', 'Too complex to use versus not interesting enough', 'Involving all services' and 'Patient involvement'. Conclusions Establishing a shared patient portal for primary and specialist health services was considered unproblematic. There was, however, variation in opinions on which content and features to include. This variation was related to concerns about increasing the workload for health care providers, causing anxiety and inequality among patients, and ensuring that the solution would be interesting enough to adopt.